(3GdYbO GdePgH aj WHbGJ MedI GdePgHs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s ((3eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg SdGeg Ydi YHGOg GdPjf GUWai s
(3GfXQg HQbe (B739 (3JGQjNs
(3HBNQgG Pjd GdeDda Ydi cJGHgs
(3fSNI KGfjI Yf fSNI GdeOjfI GdefhQI HNW eMeO Hf HgGOQ GdeDef GdWQGHdSi SfI (B869s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B297s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B185 s
Keywords: (3GdJGQjNs